2005
DOI: 10.1002/cne.20714
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of cortical subventricular zone to the development of the human cerebral cortex

Abstract: The cortical subventricular zone (SVZ), a proliferative compartment in the forebrain, has a uniquely important role during the second half of intrauterine development in human. This is best observed in numerous neonatal pathologies that result from prenatal SVZ damage. These conditions highlight a need to better understand the contribution of the SVZ to the development of the human cerebral cortex. With this goal in mind, we analyze histological organization, cell proliferation, and molecular diversity in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
208
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(224 citation statements)
references
References 85 publications
13
208
2
1
Order By: Relevance
“…Interestingly, cells immunoreactive for the calcium-binding protein calretinin, a marker for cortical GABAergic interneurons, were also detected but we did not observe any cells containing parvalbumin or calbindin (other interneuron markers). In accordance, Zecevic and co-workers [48] have reported that at mid-gestation development of the human brain, in contrast to rodents, the majority of cortical interneurons are calretinin immunoreactive. In relation to our data, one interpretation is that the neurons obtained after in vitro differentiation of hcNSCs, had not matured to the point of expressing the whole set of phenotypic markers of their in vivo counterparts.…”
Section: Discussionsupporting
confidence: 66%
“…Interestingly, cells immunoreactive for the calcium-binding protein calretinin, a marker for cortical GABAergic interneurons, were also detected but we did not observe any cells containing parvalbumin or calbindin (other interneuron markers). In accordance, Zecevic and co-workers [48] have reported that at mid-gestation development of the human brain, in contrast to rodents, the majority of cortical interneurons are calretinin immunoreactive. In relation to our data, one interpretation is that the neurons obtained after in vitro differentiation of hcNSCs, had not matured to the point of expressing the whole set of phenotypic markers of their in vivo counterparts.…”
Section: Discussionsupporting
confidence: 66%
“…Although it has been well established that the SVZ in primates produces neocortical neurons that migrate radially to the overlying cortical plate (5,10,14), recent evidence in E13 to E14 mouse embryos suggests that this secondary proliferative zone also contributes neurons to the cortical plate (9). In the present study, we confirmed this finding and, in addition, found that the SVZ cells synthesize DNA and undergo mitotic divisions even at the later stages of corticoneurogenesis (E15-E16) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The relative large size of the SVZ in primates, particularly in humans, has inspired suggestions that cells in this zone contribute to the expansion and elaboration of the neocortex during evolution (2, 10, 11). Furthermore, genetic and environmental disturbances of neuronal production in the SVZ affect the development and function of the cerebral cortex (5,(12)(13)(14).Considering the developmental and clinical significance of the SVZ, surprisingly little is known about its origin and how INPs are distinguished from other proliferative neural precursors and postmitotic migrating neurons. Similar to the postmitotic neurons, INPs leave the VZ by extending their basal processes toward the cortical plate (CP) along radial glia (RG) shafts and translocating their nuclei within the growing leading processes (1, 6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cell cultures were prepared from the VZ/SVZ of the fetal forebrain (16 gw), dissected from the frontally cut hemispheres as a tissue band approximately 2000 μm high from the VZ surface (Zecevic et al, 2005). Tissue was dissociated with 0.05% trypsin-0.02% EDTA (Invitrogen, Carlsbad, CA) and triturated through a fire-polished pipette.…”
Section: Dissociated Cell Culturementioning
confidence: 99%